Analisis Pengaruh Pertumbuhan Ekonomi, Jumlah Penduduk, Foreign Direct Investment (FDI), Energy Use/Consumption dan Krisis Ekonomi terhadap Kualitas Lingkungan Ditinjau dari Tingkat Carbon Footprint di Asean 8 - Rendria Santi; Hadi Sasana (Diponegoro Journal of Economics, 2021)
Environmental degradation is an important issue which is currently can be a threat to sustainable economic development in both developed and developing countries. Research on environmental damage due to economic development actually has been done a lot in the previous research but most of them only uses CO2 emission indicators to measure the level of environmental degradation. This study uses the concept of Ecological Footprint and more specific this study want to analyst Carbon Footprint to see the level of environmental damage. The purpose of this study was to examine the effect of economic growth, population, energy consumption, foreign direct investment (FDI) and crisis economics on Carbon Footprint in ASEAN 8 during the period 2000-2017 and to prove the existence of Environmental Kuznets Curve (EKC) shown by Inverted U-shaped. The method that used in the study is panel data regression with the Random Effect Model. The results showed that the Environmental Kuznets Curve (EKC) hypothesis was proven in ASEAN 8 countries. Population and energy consumption variables have a positive and significant effect on the level of Carbon Footprint, while foreign direct investment has a positive effect and appropiate with Pollution Heaven Hypothesis, but does not significantly affect the Carbon Footprint.